South from Guadalcanal the romance of Rennell Island - Deck, John Northcote, 1875-1957; South Sea Evangelical Mission (Toronto, Canada Evangelical, 1945)
Includes photographs.
Brethren writer and missionary.
Keywords: Brethren movement -- missionaries -- Solomon Islands